2009
DOI: 10.1002/iroh.200811093
|View full text |Cite
|
Sign up to set email alerts
|

ATP and Ergosterol as Indicators of Fungal Biomass during Leaf Decomposition in Streams: a Comparative Study

Abstract: Ergosterol and ATP concentrations, microbial respiration and sporulation rates of aquatic hyphomycetes associated with leaves of Castanea sativa decomposing in a 5 th order stream were determined periodically over a period of 102 days in order to compare ergosterol and ATP as indicators of fungal biomass. ATP and ergosterol concentrations exhibited a significant positive correlation (F = 4.459, DF = 28, P < 0.001) during the first stages of leaf breakdown (until day 39), i.e., during periods of increasing fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Ideally, ergosterol levels should strictly correlate with fungal biomass, but, depending on species and environmental conditions, the ratio of ergosterol to biomass in pure cultures can vary by a factor of up to 14 (Gessner & Chauvet, 1993; Charcosset & Chauvet, 2001; Raviraja et al , 2004). Estimates of fungal biomass based on ergosterol were up to three times higher than those calculated from ATP concentrations (Suberkropp et al , 1993); with other conversion factors, the discrepancy was less severe (Abelho, 2009). Clearly, ergosterol measurements from environmental samples have to be interpreted with caution.…”
Section: Aquatic Hyphomycetes Are Essential Providers Of Ecosystem Fumentioning
confidence: 95%
See 1 more Smart Citation
“…Ideally, ergosterol levels should strictly correlate with fungal biomass, but, depending on species and environmental conditions, the ratio of ergosterol to biomass in pure cultures can vary by a factor of up to 14 (Gessner & Chauvet, 1993; Charcosset & Chauvet, 2001; Raviraja et al , 2004). Estimates of fungal biomass based on ergosterol were up to three times higher than those calculated from ATP concentrations (Suberkropp et al , 1993); with other conversion factors, the discrepancy was less severe (Abelho, 2009). Clearly, ergosterol measurements from environmental samples have to be interpreted with caution.…”
Section: Aquatic Hyphomycetes Are Essential Providers Of Ecosystem Fumentioning
confidence: 95%
“…Selected taxonomic surveys of aquatic hyphomycetees with keys Petersen (1962, 1963a, b) Nilsson (1964) Ingold (1975) Brathen (1982, 1984 Nawawi (1985) Goh (1997) Marvanová (1997) Santos-Flores & Betancourt-López (1997) Gulis et al (2005) vary by a factor of up to 14 (Gessner & Chauvet, 1993;Charcosset & Chauvet, 2001;Raviraja et al, 2004). Estimates of fungal biomass based on ergosterol were up to three times higher than those calculated from ATP concentrations (Suberkropp et al, 1993); with other conversion factors, the discrepancy was less severe (Abelho, 2009). Clearly, ergosterol measurements from environmental samples have to be interpreted with caution.…”
Section: Taxonomy and Phylogenymentioning
confidence: 99%
“…ATP values can represent the biomass of various microorganisms, including fungi. Several investigators have used the relationship between ATP and ergosterol to obtain fungal participation in microbial biomass (Suberkropp et al 1993, Ruzicka et al 2000, Abelho 2009). We recorded a low association between ATP and ergosterol concentrations (r < 0.1) for both plant species.…”
Section: Fungal and Microbial Effects On Leaf-litter Breakdownmentioning
confidence: 99%
“…Colonization by the microbial community during the decomposition of detritus of leaves from the riparian zone of a tropical stream showed that fungi predominate in the initial stages of decomposition and that bacteria are more abundant when the leaves are already fragmented and soft (Abelho et al 2005). Abelho (2009) also reported that bacteria become gradually more important in the degradation of plant organic matter as the detritus particles become smaller. However, other studies have shown that in the initial stages of decomposition, the density of bacteria is greater than that of fungi, which become more abundant in intermediate and final stages of decomposition (Gonçalves et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies on fungi biomass quantification during macrophyte decomposition in subtropical lakes are scarce and equally needed (Carvalho et al 2015). The role played by fungi in plant decomposition has been more commonly investigated in lotic environments (e.g., Abelho et al 2005, Graça and Canhoto 2006, Gonçalves et al 2007, Abelho 2009, Sales et al 2015. In aquatic environments, fungi and bacteria are considered the main heterotrophic organisms that feed by osmotrophy from degraded plant detritus during colonization.…”
Section: Introductionmentioning
confidence: 99%